P44. Activin A is novel circulating biomarker in lung cancer - Rozsas, Anita (Transl Lung Cancer Res, 2014)
BACKGROUND: Therapeutic decision making for the treatment of lung cancer is often a complex and challenging task. Biomarkers are urgently needed that can facilitate the early detection of these malignant diseases and can predict which therapeutic modality can significantly contribute to tumor control in a given patient. METHODS: In a large cohort of lung cancer patients we collected blood samples and measured the circulating levels of activin A by ELISA. The protein level in cell supernatant and the cellular mRNA level of activin A were also analyzed in lung cancer cell lines. RESULTS: We found increased plasma activin A levels in certain patients with lung adenocarcinoma, squamous cell lung cancer and small cell lung cancer (SCLC) as well. Interestingly, activin A levels were increased in a TNM stage-dependent manner in SCLC. Furthermore, in the group of extensive SCLC disease patients, Kaplan-Meier analysis revealed that the high activin A levels were associated with significantly shorter overall survival. Secretion of activin A by lung cancer cell lines was also detected in vitro and the highest activin A level was found in a cell line isolated from a brain metastasis of a SCLC tumor. CONCLUSIONS: Our findings suggest that measurement of circulating activin A can support the diagnosis, staging and prognosis in small cell lung cancer.